CONSUMERS AND COSMETICS - BUYING PATTERN ANALYSIS IN ERODE CITY - Kalaiselvi, Dr.(Mrs) S (IJRDO -Journal of Computer Science Engineering, 2015)
In olden days people spend a lot of time in search of herbs to extract theirbenefits in order to safeguard themselves from various health hazards. In thosedays, they relied only upon natural herbs for healing. People in today’s worldare leading very busy life that they do not really have time to spend on theirexternal appearances. There are a thousand varieties of herbs that are being usedfor beauty care and medicine purpose. Examples of such herbs are Neem,Amla,Tulsi, Gooseberries, Sandalwood, Saffron and Green tealeaf etc. Peopleused these herbs as their cosmetics to satisfy the needs of the consumers, nowthere are a number of cosmetic companies in the market which produces bothchemical as well as Ayurveda bases cosmetic products. There are hugevarieties of brand available in the market. Due to the technical advancement andother industrial development in the country, there is also a lot of pollutioncausing harm to internal and external parts of the body. Skin is the mostaffected part in the human body due to environmental pollution. Even thoughthere are many chemical based cosmetics, people feel that these types ofproducts cause more harm to the skin. Ayurveda products are usually made ofnatural herbs with very minimum amount of chemicals and are less harmful tothe skin, which would reduce the side effects. Face is the reflection of an